The Role of Teachers in Handling Hyperactive Children - Risnaeni Ainunsyah; Hayani Wulandari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Early childhood is a golden age for children's development, children develop very rapidly, in this phase it is very effective for stimulus. Hyperactivity is a condition where children have excessive levels of activity, find it difficult to focus, and are impussive. Hyperactive children often move non-stop, making it difficult to sit still. Therefore, the role of teachers is very important in dealing with hyperactive children. This research examines the role of teachers in dealing with hyperactive children. The role of teachers in dealing with hyperactive children includes teachers being motivators, advisors and teachers being facilitators for children during learning. This research uses qualitative research. In this research, several techniques were also found for teachers to deal with hyperactive children, namely by giving assignments to children, praising children, and making children's hearts feel happy.